A Value Framework for the Assessment of Diagnostic Technologies: A Proposal Based on a Targeted Systematic Review and a Multistakeholder Deliberative Process in Latin America - Augustovski, Federico Ariel (2021)
Objectives: there are very few value frameworks (VFs) to assess health technologies that are focused on diagnostic tests; they usually do not reflect a multistakeholder process; and they are all developed in high-income countries. Our project performed a targeted systematic review, with the objective of proposing an evidence-based, up-to-date VF informed by a multinational multistakeholder group working in the health technology assessment (HTA) space. Methods: (1) A targeted systematic review, with the aim to identify existing VFs and their dimensions; and (2) generation a VF proposal through a mixed-methods, qualitative-quantitative approach. Results: From 73 citations identified, 20 met our inclusion criteria and served to provide the initial list of dimensions for our VF. An initial list of criteria and subcriteria for a preliminary VF was proposed. After a full-day deliberative face-to-face meeting with 30 relevant stakeholders from seven Latin American countries and the United Kingdom, the final VF was defined, consisting of 15 criteria: five “essential or core,” six highly relevant, three moderately relevant, and one of low relevance. Barriers and facilitators of value assessment of diagnostic technologies were also discussed. Conclusions: We propose a VF oriented to diagnostic technologies based on a targeted systematic review and a participatory process with key HTA stakeholders. It is the first to be produced in a lower and middle income setting but can also be potentially useful in other contexts aimed to assist decision-making processes with these particularly complex health technologies.